Nutritional and physiological responses of broiler chickens to dietary supplementation with de-oiled soyabean lecithin at different metabolisable energy levels and various fat sources. Issue 8 (28th October 2019) - Majdolhosseini, Leila; Ghasemi, Hossein Ali; Hajkhodadadi, Iman; Moradi, Mohammad Hossein
Abstract: A 42-d study was conducted to investigate the effects of an emulsifier supplementation (de-oiled soyabean lecithin (DSL)) of diets with different levels of metabolisable energy (ME) and various sources of fat on growth performance, nutrient digestibility, blood profile and jejunal morphology of broiler chickens. Diets were arranged factorially (2 × 2 × 2) and consisted of two concentrations of ME (normal and low), two fat sources (soyabean oil (SO) and poultry fat (PF)) and two levels of DSL supplementation (0 and 1 g/kg). A total of 800 1-d-old male broiler chickens were assigned to eight treatments with five replicates/treatment. The results showed the supplemental DSL caused improvements in the overall feed conversion ratio, fat digestibility and jejunal villus height:crypt depth ratio, but the magnitude of the responses was greater in the PF-containing diets, resulting in significant fat × DSL interactions ( P <0·05). Abdominal fat percentage was also reduced by the PF-containing diet, but the response was greater in the normal ME diet, resulting in a significant ME × fat interaction ( P = 0·048). Dietary DSL supplementation also increased nitrogen-corrected apparent ME values but decreased blood TAG ( P = 0·041) and LDL ( P = 0·049) concentrations, regardless of the source of fat used or the ME values in the diet. In conclusion, the present study suggests that the improvements in growth performance, fat digestibility and intestinal morphology that can be achieved with DSL supplementation are highly dependent on the degree of saturation of lipid incorporated into broiler chicken diets.